2020
DOI: 10.1302/0301-620x.102b3.bjj-2019-1325.r1
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the outcomes of tibiotalocalcaneal fusion

Abstract: Aims Tibiotalocalcaneal (TTC) fusion is used to treat a variety of conditions affecting the ankle and subtalar joint, including osteoarthritis (OA), Charcot arthropathy, avascular necrosis (AVN) of the talus, failed total ankle arthroplasty, and severe deformity. The prevalence of postoperative complications remains high due to the complexity of hindfoot disease seen in these patients. The aim of this study was to analyze the relationship between preoperative conditions and postoperative complications in order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 38 publications
0
15
0
4
Order By: Relevance
“…In another recent retrospective review of 101 patients undergoing open TTC fusion with various approaches, they found an infection rate of 37% and 29.6% for patients with nontraumatic osteoarthritis and Charcot arthropathy, respectively. 18 Additionally, 5 patients (4.9%) went on to require below-knee amputations. 18 Although there may be significant heterogeneity when comparing patients undergoing open and minimally invasive TTC fusion, transportal TTC fusion should be considered in patients with significant comorbidities, particularly those with diabetes mellitus, as it leads to low rates of surgical site infections and thereby may reduce the risk of severe complications such as amputations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In another recent retrospective review of 101 patients undergoing open TTC fusion with various approaches, they found an infection rate of 37% and 29.6% for patients with nontraumatic osteoarthritis and Charcot arthropathy, respectively. 18 Additionally, 5 patients (4.9%) went on to require below-knee amputations. 18 Although there may be significant heterogeneity when comparing patients undergoing open and minimally invasive TTC fusion, transportal TTC fusion should be considered in patients with significant comorbidities, particularly those with diabetes mellitus, as it leads to low rates of surgical site infections and thereby may reduce the risk of severe complications such as amputations.…”
Section: Discussionmentioning
confidence: 99%
“… 18 Additionally, 5 patients (4.9%) went on to require below-knee amputations. 18 Although there may be significant heterogeneity when comparing patients undergoing open and minimally invasive TTC fusion, transportal TTC fusion should be considered in patients with significant comorbidities, particularly those with diabetes mellitus, as it leads to low rates of surgical site infections and thereby may reduce the risk of severe complications such as amputations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study containing 10 patients showed that patients with CKD were 2.37 times more likely to have a nonunion from tibiotalocalcaneal fusion. 28 Of note, the comparison group used in this study was patients without CKD. One way to guide surgical decision making in patients with CKD may be to apply osteologic parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are studies that report TTC fusion as having an improvement in functional scores, 4 , 15 these procedures can be surgically challenging, with varied functional outcomes and high rates of reported nonunion and reoperation. 4 , 14 , 15 …”
Section: Introductionmentioning
confidence: 99%